UNVEILING FUTURE PATHWAYS IN ESG AND SUSTAINABILITY: A BIBLIOMETRIC EXPLORATION OF EMERGING TRENDS AND RESEARCH GAPS - Lusy; Ginting, Rafles (Faculty of Economics and Business University of Mataram, 2025)
This study aims to identify future research opportunities in the field of sustainability and ESG through a bibliometric analysis of Scopus articles for the period 2014-2024, focusing on the fields of business, management, and accounting. The results show that the dominant topics are sustainable development, CSR, and governance, while ESG investment, financial performance, and new technologies are still under-explored. Driven by stakeholder expectations, regulations, and the need for legitimacy for ESG adoption, in line with stakeholder theory, legitimacy theory, and natural resource-based approach (NRBV). This study highlights the need for the development of standardized ESG metrics, increasing regional diversity, and cross-disciplinary integration to strengthen the understanding and implementation of sustainability. This study contributes to bridging the research gap, identifying emerging trends, developing an ESG roadmap and developing more effective sustainability strategies.